2018
DOI: 10.3390/nu10101454
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Blood or Erythrocyte Membrane Fatty Acids for Disease Risk Prediction: Focusing on Cardiovascular Disease and Chronic Kidney Disease

Abstract: Fatty acids (FAs) are essential nutrients and main constituents of cell membranes that are involved in the signaling pathway and associated with health conditions. We investigated if blood or erythrocyte membrane FAs can predict the risk of cardiovascular disease (CVD), chronic kidney disease (CKD), and related complications. Omega-3 (n-3) FAs are important predictors for metabolic syndrome, diabetes, CVD, and CKD risks, and the n-3 index is also a good biomarker for sudden cardiac death in coronary artery dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 109 publications
0
20
0
Order By: Relevance
“…Currently, there are minimal data on the effects that impaired renal function may have on PUFA metabolism and physiology. However, it has been reported that consumption of n‐3 PUFA is beneficial in patients with chronic kidney disease and may reduce serum triacylglycerols, inflammation, and cardiovascular risk (Kim et al, ). Studies specific to patients with PAD are more limited, but report similar results (Grenon et al, ) in addition to increases in the O3I and downstream lipid mediators of resolution of inflammation (Grenon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are minimal data on the effects that impaired renal function may have on PUFA metabolism and physiology. However, it has been reported that consumption of n‐3 PUFA is beneficial in patients with chronic kidney disease and may reduce serum triacylglycerols, inflammation, and cardiovascular risk (Kim et al, ). Studies specific to patients with PAD are more limited, but report similar results (Grenon et al, ) in addition to increases in the O3I and downstream lipid mediators of resolution of inflammation (Grenon et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…2 : Ratio of monounsaturated fatty acid to total fatty acid. 3 : Ratio of polyunsaturated fatty acid to total fatty acid. 4 : Ratio of omega-3 fatty acid to total fatty acid.…”
Section: General Characteristics Of the Populationmentioning
confidence: 99%
“…These 2 families each encompass fatty acids with varying carbon chain length and degree of unsaturation. Supplemental Figure S1 shows PUFA biosynthesis, detailing the omega-6 and omega-3 pathways and the names of the main PUFA, as well as the elongation and the desaturation activities [1][2][3]. Briefly, the omega-6 PUFA linoleic acid (LA) and the omega-3 PUFA alpha-linolenic acid (ALA) from the diet are the key substrates that enter the pathways leading to the synthesis of the main long-chain PUFA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, longitudinal studies are required to test the robustness of the findings of this study. Moreover, accumulating data for the involvement of lipid composites besides TC, TG, HDL-C, and LDL-C are found in the literatures (31,32), suggesting that novel lipid biomarkers for eGFR not covered in the present study still need to be investigated.…”
Section: Discussionmentioning
confidence: 93%